Confederated cloud—Design consideration for distributed utility computing system of systems. Issue 3 (10th October 2018) - Biran, Yahav; Dubow, Joel
Abstract: Cloud computing advances are enabling cloud tenants to host and process their IT workloads in a safe, reliable, and cost‐effective manner. Federated clouds help cloud providers optimize many business parameters such as computing resource utilization. Federated clouds also introduce business risks to the cloud service providers in situations such as fewer tenants and various misconfigurations of energy, security, and load distributions arising from some possible sources. Yet, the rewards outweigh the risks when the federation implementation is successful. This work proposes a different optimization strategy that clarifies and simplifies the design trade‐offs for the federated clouds. We call it the confederated cloud. The strategy for it is to recruit customer groups by providing domain‐specific market services to cloud service providers that have a common market or business characteristics. The confederation will be a federation of domain groups, thus forming an interim cloud grouping that will retain domain‐specific privacy and governance structure and the confederation structure provide services on a more efficient or cost‐effective basis than can individual cloud service providers. This will help cloud providers to increase their datacenter resource utilization, decrease energy consumption, improve security, and increase revenue. It will also support cloud providers to set a suitable computing price for each computing resource type that matches the specific cloud group domain requirements. This solution will enable domain‐specific tenant groups to maintain controls of what is competitively vital and pool resources where it is advantageous to do so. The resulting architecture will be a decentralized system of systems that offers multicloud providers deployments similar to the centralized cloud federation. The confederated cloud system of systems described introduces a new system of systems engineering paradigm that uses domain‐specific governance for otherwise open communities that collaborate throughout the system life cycle. The confederated cloud system of systems has no explicit requirements for the cloud provider and cloud providers will not be aware of confederation services. Nonetheless, cloud providers might also not be aware of such system of systems. A successful confederated cloud will advantageous for many tenants. This enhanced market for cloud providers will help advance and drive the evolution of federated clouds.